IMPLEMENTASI PENDIDIKAN AGAMA ISLAM BERBASIS KEARIFAN LOKAL DI MADRASAH IBTIDAIYAH ANDALAN CIJANTUNG KABUPATEN CIAMIS - Dini Apriliani Khairunissa Gurnadi (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to describe and analyze the implementation of local wisdom-based Islamic Religious Education in Madrasah Ibtidaiyah and its contribution to the character formation of students. The background of this study is based on the importance of religious education that is not only oriented towards mastering normative Islamic knowledge, but also able to integrate local cultural values ​​that live and develop in the community. This study uses a qualitative approach with descriptive methods. Data collection was carried out through observation, in-depth interviews, and documentation with research subjects including the madrasah principal, Islamic Religious Education teachers, and students. The results of the study indicate that the implementation of local wisdom-based Islamic Religious Education is carried out through the integration of local cultural values ​​into the materials, methods, and learning activities, such as habituating religious attitudes, social activities, and the application of local traditions that are in line with Islamic teachings. This approach makes learning more contextual and meaningful for students. In addition, the implementation of local wisdom-based Islamic Religious Education has a positive impact on the formation of student character, especially in aspects of religiosity, discipline, social awareness, and mutual respect. However, this study also identified several obstacles, including limited relevant learning resources and suboptimal teacher competency in developing local wisdom-based learning. Therefore, policy support, teacher competency strengthening, and the development of sustainable madrasah culture are needed to optimize the implementation of local wisdom-based Islamic Religious Education in Madrasah Ibtidaiyah (Islamic Elementary Schools).